Congregational Singing as Social Identity Shaping in Toronto Cantonese Worship Services - Mok, Carson Ka Shing (My University, 2023)
Congregational singing is widely acknowledged as a doxology to God. Yet, opinions differ on how congregational singing influences the worshippers’ lives. Some believe that the group singing prepares the heart for the sermon, while others believe it has formational implications. This project explores the formative qualities in congregational singing, specifically emphasizing how such group activity informs the worshipper’s identity with God and how the worshipper relates to others through God. Biblical identities are utilized as the theological perspective to examine the identity messages expressed in congregational singing. The idea of identity hierarchy in social psychology, which includes social association and identity renegotiation, is used as the theoretical framework. This research strives to conduct critical inquiry and reflection on the theological, theoretical, and practical orientation of congregational singing in Greater Toronto Area Cantonese worship services. As such, a literature review concerning the theology, theory, and practice of congregational singing is discussed, from which implications are drawn to the research design process. Participant observation, online questionnaire, and qualitative interview methods are used to help extract and analyze how the social identity shaping process occurs in congregational singing within the research context.